High Performance Organic Electrochemical Transistors and Logic Circuits Manufactured via a Combination of Screen and Aerosol Jet Printing Techniques. Issue 10 (31st May 2022) - Makhinia, Anatolii; Hübscher, Kathrin; Beni, Valerio; Andersson Ersman, Peter
Abstract: This work demonstrates a novel fabrication approach based on the combination of screen and aerosol jet printing to manufacture fully printed organic electrochemical transistors (OECTs) and OECT‐based logic circuits on PET substrates with superior performances. The use of aerosol jet printing allows for a reduction of the channel width to ≈15 µm and the estimated volume by a factor of ≈40, compared to the fully screen printed OECTs. Hence, the OECT devices and OECT‐based logic circuits fabricated with the proposed approach emerge with a high ON/OFF ratio (10 3 –10 4 ) and remarkably fast switching response, reaching an ON/OFF ratio of >10 3 in 4–8 ms, which is further demonstrated by a propagation delay time of just above 1 ms in OECT‐based logic inverter circuits operated at a frequency of 100 Hz. All‐printed monolithically integrated OECT‐based five‐stage ring oscillator circuits further validated the concept with a resulting self‐oscillation frequency of 60 Hz. Abstract : Here, a novel fabrication approach is demonstrated and compared. The combination of screen and aerosol jet printing techniques allows for the manufacturing of all‐printed organic electrochemical transistors (OECTs) and more advanced cascade‐coupled logic circuits. The reported propagation delay (≈1 ms at 100 Hz) and self‐oscillation frequency (≈60 Hz) are clearly beyond the achievements in previously reported fully screen printed OECT‐based circuits.